2019
DOI: 10.1371/journal.pone.0211808
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical atherosclerosis in psoriasis. Usefulness of femoral artery ultrasound for the diagnosis, and analysis of its relationship with insulin resistance

Abstract: BackgroundPsoriasis is associated with an increased risk of cardiovascular disease (CVD) at younger ages that is not identifiable by traditional risk factors. Screening for subclinical atherosclerosis with ultrasound has only been investigated in carotid arteries. Femoral artery ultrasound has never been considered for this purpose. The link between psoriasis and accelerated atherosclerosis has not yet been established.ObjectiveTo study the usefulness of femoral artery ultrasound for the detection of subclinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…In these studies, patients with moderate‐to‐severe psoriasis demonstrate subclinical inflammation in the liver, joints and tendons, in addition to significantly increased global arterial and subcutaneous inflammation, and patients with mild psoriasis had subclinical inflammation in the aorta . Also, ultrasound of femoral arteries can improve detection of subclinical atherosclerosis in patients with moderate‐to‐severe psoriasis and insulin resistance helps to provide a better prediction of subclinical atherosclerosis than traditional CVD risk factors . Such observations have led to a better understanding of how a subset of inflammatory molecules diffuse into the systemic circulation and then to various organ systems; this may contribute to the pathology of common inflammatory comorbidities in psoriasis (Fig.…”
Section: Psoriasis: a Systemic Inflammatory Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…In these studies, patients with moderate‐to‐severe psoriasis demonstrate subclinical inflammation in the liver, joints and tendons, in addition to significantly increased global arterial and subcutaneous inflammation, and patients with mild psoriasis had subclinical inflammation in the aorta . Also, ultrasound of femoral arteries can improve detection of subclinical atherosclerosis in patients with moderate‐to‐severe psoriasis and insulin resistance helps to provide a better prediction of subclinical atherosclerosis than traditional CVD risk factors . Such observations have led to a better understanding of how a subset of inflammatory molecules diffuse into the systemic circulation and then to various organ systems; this may contribute to the pathology of common inflammatory comorbidities in psoriasis (Fig.…”
Section: Psoriasis: a Systemic Inflammatory Diseasementioning
confidence: 99%
“…[20][21][22] Also, ultrasound of femoral arteries can improve detection of subclinical atherosclerosis in patients with moderate-to-severe psoriasis and insulin resistance helps to provide a better prediction of subclinical atherosclerosis than traditional CVD risk factors. 23 Such observations have led to a better understanding of how a subset of inflammatory molecules diffuse into the systemic circulation and then to various organ systems; this may contribute to the pathology of common inflammatory comorbidities in psoriasis ( Fig. 2).…”
Section: Psoriasis: a Systemic Inflammatory Diseasementioning
confidence: 99%
“…Insulin resistance induced by the inflammatory response in psoriasis can cause atherosclerosis. Research showed that a variety of inflammatory markers can be detected in the blood of patients with psoriasis, confirming that the body was in a systemic inflammatory state during the onset of psoriasis, which induced insulin resistance and reduced the release of vasodilator factors, then it provided an environmental basis for the formation of atherosclerotic plaques ( 19 ). Studies have shown that psoriasis is associated with atherosclerosis through dyslipidemia, including increased levels of total cholesterol, triglycerides, low-density lipoprotein, ultra-low-density lipoprotein and lipoprotein a, and the reduction of high-density lipoprotein and apolipoprotein B levels ( 20 ).…”
Section: Discussionmentioning
confidence: 97%
“…40) Moreover, ultrasound can be used to detect subclinical atherosclerosis in femoral arteries. Gonzalez-Cantero et al 41) demonstrated that femoral atherosclerotic plaque was more prevalent in patients with psoriasis than in those without, and that it was more prevalent than carotid plaque, thereby improving its detection in subclinical stages. These data make ultrasound a low-cost, high-performance technique that allows assessment of atherosclerotic damage in patients with psoriasis.…”
Section: Imaging In the Evaluation Of Cardiovascular Diseasementioning
confidence: 99%